2015
DOI: 10.3389/fgene.2015.00026
|View full text |Cite
|
Sign up to set email alerts
|

Shared genetic variance between obesity and white matter integrity in Mexican Americans

Abstract: Obesity is a chronic metabolic disorder that may also lead to reduced white matter integrity, potentially due to shared genetic risk factors. Genetic correlation analyses were conducted in a large cohort of Mexican American families in San Antonio (N = 761, 58% females, ages 18–81 years; 41.3 ± 14.5) from the Genetics of Brain Structure and Function Study. Shared genetic variance was calculated between measures of adiposity [(body mass index (BMI; kg/m2) and waist circumference (WC; in)] and whole-brain and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 66 publications
(98 reference statements)
0
23
1
Order By: Relevance
“…BMI is often associated with reduced white matter microstructure (Ryan et al, 2017;Spieker et al, 2015;Stanek et al, 2011) and higher circulating levels of IL-6, IL-8, and TNFα (Bruun, Pedersen, Kristensen, & Richelsen, 2002;Bruun, Verdich, Toubro, Astrup, & Richelsen, 2003;Straczkowski et al, 2002), making it an important factor to consider in genetic correlation models. Indeed, in our sample BMI was phenotypically correlated with IL-6, TNFα, and a few white matter tracts and genetically correlated with IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…BMI is often associated with reduced white matter microstructure (Ryan et al, 2017;Spieker et al, 2015;Stanek et al, 2011) and higher circulating levels of IL-6, IL-8, and TNFα (Bruun, Pedersen, Kristensen, & Richelsen, 2002;Bruun, Verdich, Toubro, Astrup, & Richelsen, 2003;Straczkowski et al, 2002), making it an important factor to consider in genetic correlation models. Indeed, in our sample BMI was phenotypically correlated with IL-6, TNFα, and a few white matter tracts and genetically correlated with IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…In previous research, these traits have shown high heritability and significant genetic correlation with measures of brain integrity (Glahn et al, ; Kochunov et al, , ). We also considered body mass index (BMI) and systolic and diastolic blood pressures based on research linking body adiposity to cerebral integrity (Kochunov, Glahn, Lancaster, et al, ; Ryan et al, ; Spieker et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The main goal was to assess whether the aforementioned obesity-neurobehavioural associations are of genetic or environmental origin. Recent evidence from behavioural and molecular genetics suggests that there is considerable genetic overlap between obesity, cognitive test scores, and brain imaging findings (15)(16)(17)(18)(19)(20). However, the evidence so far is not comprehensive across all neurobehavioural factors discussed.…”
Section: Introductionmentioning
confidence: 99%